A challenge of incentive for small hydropower commercial investment in Thailand. (October 2017) - Supriyasilp, Thanaporn; Pinitjitsamut, Montchai; Pongput, Kobkiat; Wanaset, Apinya; Boonyanupong, Suree; Rakthai, Saksri; Boonyasirikul, Thana
Abstract: Thailand implemented a premium-price Feed-in Tariff (FIT), or 'Adder' program, in 2006 as an incentive to generate renewable energy. However, the Adder rate for hydropower was very low, and failed to motivate investors. Later, the Thai government decided to change the Adder program to a fixed-price FIT instead. As of 2014, no studies had analysed hydroelectric power rates in Thailand. Therefore, the objective of this study is to determine the suitable rate for a fixed-price FIT for hydropower in Thailand, using the concept of the actual levelized cost of renewable energy generation. The results showed that the structure of the FIT rate was comprised of three elements: installed capacity, hydropower scheme, and grid connection. From experience with the Adder program, the rate will not be limited at only 200 kW. The proposed rate offers a steady annual return for over 25 years. The recommended rate provides an IRR of 12%, with water fee included. Moreover, we recommend an exclusive promotion rate to promote partnerships with, and to motivate, local communities to conserve and manage the water resource. Furthermore, we suggest using a guideline for calculating social cost-benefits as avoided costs, as well as allocating social benefits. Highlights: This study examines fixed price feed-in tariffs for hydroelectricity. The tariff rate is based on capacities, hydropower schemes, and grid connection. A joint investment project will also receive an exclusive promotion rate. The avoided costs and carbon emission costs are considered as social benefits. The social benefits should be returned to electricity users.